(untitled) (Libya Journal of Geographical Studies, 2023)
The problem of food security emerged as one of the dilemmas that imposed itself, on the international arena, especially in the Arab countries, and there was a shortage of foodstuffs due to the Corona delinquency, and disturbances in international trade, and Libya suffers from two basic problems in the field of food, The decrease in the area of ​​agricultural lands and the lack of water, compared to human needs, and as a result the inability, of the local agricultural sector to meet the volume of demand for food, and there dependence on oil revenues to provide food from abroad. This study aimed at clarifying the natural and human characteristics, and their impact on the practice of marine fishing, and tracking the development of fish production in northwest Libya, and its role in achieving food security. From what the study concluded, the fish sector faces great challenges that prevent its effective contribution to achieving food security, especially with regard to the decline, in the number of workers in the field of marine fishing, as well as a decrease in fishing units in recent years, in addition to a decrease in the number of fisheries workers. The value of financial allocations for this sector, The study came out with a number of recommendations, most notably encouraging job seekers to go to practice the fishing craft, providing them with material incentives, and working to eliminate illegal immigration, so that the fishing units continue to practice their work in a regular way, and the establishment of modern ports dedicated to marine fishing.